Pembangunan dan Penilaian Instrumen Kesihatan Mental dan Kecerdasan Spiritual - Ahmad Muhaimin Mohamad; Rohana Hamzah; Paridah Mohd Ali; Hadijah Ahmad; Norizan Yusof; Haslinda Hashim; Muhammad Salehan Alhafiz Mat Wajar (USIM Press, 2024)
Jurnal Sains Insani Volume 8 No 2 Page (338-349)